Bibliometric Analysis on Green Workforce Readiness - Judijanto, Loso (Westscience Press, 2025)
This study presents a bibliometric analysis of the scholarly literature on green workforce readiness, a critical area in the transition toward sustainable and low-carbon economies. Using data extracted from the Scopus database and analyzed through VOSviewer, the study maps key publication trends, co-occurring themes, leading authors, and international collaboration networks. The results indicate that